The Effect of Women's Empowementand Realization of Their Rights: A Case Study of Nasuuti Sub-County, Mukono District - Harriet Juan Wani Ombasa (Uganda Christian University, 2023)
This study investigates the Relationship between the Promotion of Women's Empowerment and the Realization of their Rights in Nasuti Sub-County, Mukono District. The research assesses the perspectives of respondents on key statements related to women's empowerment and rights. The findings from Table 4.5 indicate that a significant proportion of respondents strongly agree that women have equal opportunities as men and that opportunities for women have been established to promote their empowerment and rights. However, the study also reveals a lack of consensus on whether the provision of capital to women effectively promotes empowerment and rights. Additionally, the study explores possible solutions to the challenges facing the promotion of women's empowerment and realization of their rights in the same region. Table 4.6 illustrates that enhancing women's skills and providing them with education and capital are perceived as viable solutions. However, there is uncertainty among respondents regarding the importance of proper sensitization. Furthermore, the research identifies the major challenges hindering women's empowerment and rights in Table 4.7. Respondents strongly agree that increasing ignorance among men and negative perceptions about women's education are significant challenges. Unequal access to education is also recognized as a key barrier, while domestic violence is acknowledged as a concern but not universally agreed upon.This study concludes by emphasizing the importance of addressing these challenges to enhance women's empowerment and rights in Nasuti Sub-County, Mukono District. It suggests that efforts should focus on providing women with skills and education, dispelling negative perceptions, and addressing gender-based violence. These findings have implications for policy and program development to promote gender equality and women's rights.
This is a dissertation.